UNDERSTANDING: THE NATURE OF NURTURE - PART 2 - Miller, Ronald (PINS-Psychology in Society, 2026)
That we learn from others is less a scintillating or profound idea than a common-place acknowledgement of the human condition. Yet it is not uncommon to find this self evident truth attributed to Vygotsky as if it were a major discovery that had long eluded centuries of thought and reflection about human nature. Outside the halls of arcane academic discourse, few would claim that we actually name ourselves, invent our own languages that miraculously are understood by others. devise our own belie/ systems and construct all the tools of our various trades, and all this all by our singular selves. Leaving aside potted versions of Vygotsky that reflect the most superficial interpretations of his subtle and intriguing theories and ideas, if originality is at issue then it Is surely Piaget who must take the honours for providing a counter-intuitive account of human learning. Piaget’s insight was that despite the obvious and necessary fact of social or cultural learning and the role of others in the child’s development, cultural and social factors are not sufficient to explain learning. This distinction between the necessary and the sufficient finds expression in Piaget’s use of the terms learning and development to Indicate the difference. Piaget’s theory that relies on a method designed to eliminate or minimize cultural and social factors, is intended not only to provide an account of the sufficient conditions that underpin cognitive development but also to plug the theoretical hole that any account based on the primacy of social learning must confront. This is the infinite regress of the teacher’s teacher or the other’s other. The problem is not only theoretical in the formal or logical sense but presents a problem for evolutionary psychology where human culture and language cannot be relegated to a given whose genesis does not require any explanation.